Application of Lactiplantibacillus plantarum SCH1 for the Bioconservation of Cooked Sausage Made from Mechanically Separated Poultry Meat - Beata Łaszkiewicz; Piotr Szymański; Dorota Zielińska; Danuta Kołożyn-Krajewska (Applied Sciences, 2021)
The aim of the research was an assessment of the effect of the Lactiplantibacillus plantarum SCH1 strain isolated from ecological raw fermented pork roast on pH, redox potential, nitrites, and nitrates content, L a* b* color parameters, total heme pigments content, nitrosyl myoglobin concentration, as well as the microbiological quality and sensory traits of cooked sausages produced from mechanically separated poultry meat (MSPM), cured with a lower sodium nitrite level (NaNO2 50 mg/kg) after production as well as after storage (1 and 3 weeks of storage). The biochemical identification of the Lactobacillus bacteria after storage was also performed. Tests were performed in two sausage treatments: C—control sausage made from MSPM and L—sausage made from MSPM inoculated with L. plantarum at approx. 107 cfu/g. No negative effect of using the L. plantarum SCH1 strain on the physical and chemical MSPM sausage features was found. The treatment with L. plantarum SCH1 was of better microbiological quality after 3 weeks of storage. The sausages with L. plantarum SCH1 kept good sensory quality while the control treatment was spoiled after storage.